2019
DOI: 10.4022/jafib.2233
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Quantification of Vagal Denervation by Extracardiac Vagal Stimulation during Second Generation Cryoballoon ablation: a Vein per Vein Analysis

Abstract: Radiofrequency ablation (RFA) for atrial fibrillation (AF) has emerged as an effective and reliable treatment modality. Since its introduction in the 1990s, major and minor complications have been identified. Major complications include periprocedural death, atrioesophageal (AE) fistula, stroke, cardiac perforation and tamponade, pulmonary venous stenosis, phrenic nerve injury, retroperitoneal hematoma, and arrhythmias. Minor complications include pseudoaneurysms and arteriovenous fistulas. We report an extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A previous study that quantified substrate modification in the LA using high‐density mapping, demonstrated that approximately 60% of the LA posterior wall was modified by CBA in the LA roof line 4 . CBA in the LA roof may also affect the ganglionated plexus 18 . These additional effects of CBA may contribute to the high AF‐free survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study that quantified substrate modification in the LA using high‐density mapping, demonstrated that approximately 60% of the LA posterior wall was modified by CBA in the LA roof line 4 . CBA in the LA roof may also affect the ganglionated plexus 18 . These additional effects of CBA may contribute to the high AF‐free survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…4 CBA in the LA roof may also affect the ganglionated plexus. 18 These additional effects of CBA may contribute to the high AF-free survival rate.…”
Section: La Roof Ablation With Cryoballoonmentioning
confidence: 99%